Anti-Inflammatory Effect of Phyllanthus niruri: A Meta-Analysis - Susanti, R; Fitriya, Farikhatun Nur; Kristamtini, K; Utomo, Didik Huswo (Biosaintifika: Journal of Biology & Biology Education, 2024)
Many studies report on the role of Phyllanthus niruri as an anti-inflammatory and there are variations in the results in every research, so a meta-analysis study is needed to obtain accurate results. This study aims to conduct a meta-analysis of the effect of Phyllanthus niruri as an anti-inflammatory. This study uses a meta-analysis research design with data collection from 12 databases. The screening process was carried out according to PRISMA, then analyzed using Comprehensive Meta-Analysis Version 3 (CMA3). Funnel plot and Egger’s test were used as methods to measure publication bias. The articles used were 438 articles from various research journals. After going through screening, as many as 5 articles were eligible to be incorporated in the meta-analysis. Data were analyzed using a random effect model to calculate standardized means difference (SMD). The cytokines analyzed were TNF-α and IL-6 because both were discussed in at least 3 studies. Phyllanthus niruri affected the reduction of inflammatory cytokines with an effect size of SMD on TNF-α is -17,611 (95% CI -29,347, -5,875; p=0.003) and IL-6 is -3,263 (95% CI -5,403, -1,222; p = 0.003). The results of this meta-analysis strengthen the concept/theory that Phyllanthus niruri has the potential as an anti-inflammatory by reducing the inflammatory cytokines TNF-α and IL-6. These results strengthen the scientific basis for the use of Phyllanthus niruri as a supplement for the community to prevent inflammation.